Robot-assisted therapy for upper extremity rehabilitation in Erb-Duchenne palsy: A case report - AVCI, ENDER ERSİN; AKGÜN, İREM; TİMURTAŞ, EREN; DEMİRBÜKEN, İLKŞAN; POLAT, MİNE GÜLDEN (My University, 2020)
Erb-Duchenne palsy (EDP), happens during a difficult birth due to the lesion in the upper brachial plexus (involving 5thand 6th, and rarely 7th cervical nerve roots), is characterized by muscle weakness and loss of motor functions in the affected upper extremity. While some injuries are temporary with full recovery, some may be lifelong resulting in significant functional limitations in daily life [1]. Various conservative rehabilitation approaches including muscle strength and range of motion training in upper extremity have been widely used in rehabilitation clinics [2]. Robot-assisted therapy (RAT) as an intervention for upper extremity rehabilitation is an encouraging approach in order to improve upper limb function in patients with neurological impairments [3]. RAT would offer motivational and intensive rehabilitation for a pediatric patient with EDP to interact and train with task-related games in the robotic devices.
Keywords: Sağlık Bilimleri; Fizyoterapi ve Rehabilitasyon; Health Sciences; Physical therapy and rehabilitation; Klinik Tıp (MED); Klinik Tıp; REHABİLİTASYON; Clinical Medicine (MED); CLINICAL MEDICINE; REHABILITATION; Fizik Tedavi, Spor Terapisi ve Rehabilitasyon; Kayropraktik; Rehabilitasyon; Physical Therapy, Sports Therapy and Rehabilitation; Chiropractics; Rehabilitation